2012
DOI: 10.1186/1556-276x-7-367
|View full text |Cite
|
Sign up to set email alerts
|

Room light anodic etching of highly doped n-type 4 H-SiC in high-concentration HF electrolytes: Difference between C and Si crystalline faces

Abstract: In this paper, we study the electrochemical anodization of n-type heavily doped 4 H-SiC wafers in a HF-based electrolyte without any UV light assistance. We present, in particular, the differences observed between the etching of Si and C faces. In the case of the Si face, the resulting material is mesoporous (diameters in the range of 5 to 50 nm) with an increase of the ‘chevron shaped’ pore density with depth. In the case of the C face, a columnar morphology is observed, and the etch rate is twice greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 18 publications
0
26
1
Order By: Relevance
“…The SiC etching mechanism proposed by Shor and Kurtz 16 has been generally accepted. 13,[17][18][19][20][21][22][23] According to their hypothesis, anodic etching of SiC in aqueous HF occurs in two steps: oxidation of SiC and dissolution of the formed oxide. They suggested that oxidation of SiC occurs via the following reactions: 16 SiC…”
Section: Methodsmentioning
confidence: 99%
“…The SiC etching mechanism proposed by Shor and Kurtz 16 has been generally accepted. 13,[17][18][19][20][21][22][23] According to their hypothesis, anodic etching of SiC in aqueous HF occurs in two steps: oxidation of SiC and dissolution of the formed oxide. They suggested that oxidation of SiC occurs via the following reactions: 16 SiC…”
Section: Methodsmentioning
confidence: 99%
“…This setup was described in previous work. 11 In this case, the back side contact is ensured by the electrolyte. In the case of high doping levels, the anodization can be conducted without any additional lighting.…”
Section: Methodsmentioning
confidence: 99%
“…However, a pore enlargement occurs when the applied current density increases. 11 At first, porous samples were prepared according to the following cleaning procedure. The substrates were sequentially cleaned in a H 2 SO 4 (96%) : H 2 O 2 (1:1) solution at 120 • C during 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The substrate removal was obtained by electrochemical etching. ECE is an oxidation/oxide-removal process obtained by dipping the SiC wafer in a hydrofluoridric acid-based solution and electrically supply holes for the oxidation through a 100 nm aluminium back metal contact [6,[21][22][23]. The process is capable of removing highly doped (≥ 10 18 cm −3 ) p-type and n-type layers but is selective towards low-doped n-type layers (selectivity > 1000:1 with respect to the 5 × 10 13 cm −3 doped n − layer).…”
Section: Sample Preparationmentioning
confidence: 99%